Nutrition in Health and Disease Our Challenges Now and Forthcoming Time - Mózsik, Gyula; Figler, Mária (IntechOpen, 2019)
This book deals with very different aspects of nutrition from different countries (qualities and quantities of food, their absorptions from the gastrointestinal tract, utilization in healthy human beings or in patients with different diseases, food and drug interactions, etc.). However, these different nutritional positions are different in the different countries. The 13 chapters were written by experts from countries in four continents (Asia, Africa, America, and Europe) and generally cover one nutritional problem each; however, if we analyze the results of all the chapters, we can see the most important nutritional problems from all over the world. This detailed analysis offers us an overview of this most urgent nutritional problem.We know that the world's population has increased exponentially in the last few decades (and is still increasing); however, foods and food products have increased more slowly. We have to solve these and other nutritional problems to ensure the health of generations to come.